Acerca de los informes crediticios y su regulación argentina - Fernández, Diego (2024)
In Argentina, the Personal Data Protection Law No. 25,326, along with its Regulatory Decree No. 1558/2001, introduces in its Article 26 norms related to the provision of credit services, imposing obligations on data controllers and recognizing rights to data subjects. In this article, we will analyze the current regulatory framework, offering comments from a comparative law perspective. We will examine legislation in the region and in European Union countries. We will also review the most relevant jurisprudential cases in Argentina related to the provision of credit services under Law No. 25,326, and the interpretation of the supervisory authority regarding Article 26. We will finally review the different proposed reforms to Article 26 presented in the Argentine Congress, with emphasis on the project to replace Law No. 25,326, recently introduced by the Executive Branch, and on the modifications that said project introduces regarding the creation of credit reports.